2008
DOI: 10.1007/s11240-008-9492-8
|View full text |Cite
|
Sign up to set email alerts
|

Wood formation during ex vitro acclimatisation in micropropagated true service tree (Sorbus domestica L.)

Abstract: Micropropagated plantlets derived from a superior 90?-year-old slow-growing true service tree (Sorbus domestica L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
13
1
1
Order By: Relevance
“…Moreover TDZ has been reported to be appropriate in in vitro proliferation step of some prunus spp. [23]. It is worth mentioning that some investigators have reported that TDZ and BA are the cytokinins used the most [12], while Arinaitwe et al [17] and Go´ral-ski et al [18] reported that kinetin and isopentenyl adenine (2iP) have been used less.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover TDZ has been reported to be appropriate in in vitro proliferation step of some prunus spp. [23]. It is worth mentioning that some investigators have reported that TDZ and BA are the cytokinins used the most [12], while Arinaitwe et al [17] and Go´ral-ski et al [18] reported that kinetin and isopentenyl adenine (2iP) have been used less.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular characteristics were determined from SEM images for the sixth annual growth ring (both hybrids) and the seventh annual growth rings (‘Dodoens’ trees only) using the NIS-Elements AR 3.0 image analysis software (Laboratory Imaging, Prague, Czech Republic) as described by Ďurkovič and Mišalová [ 30 ]. The traits such as vessel lumen area ( A ), vessel density per square millimeter of wood ( N ), radial and tangential diameters of vessels were determined for earlywood and latewood separately.…”
Section: Methodsmentioning
confidence: 99%
“…(), rinsed with water, dehydrated in an ascending ethanol series, rinsed with xylene, mounted in a drop of Clarion mounting medium beneath a coverslip, and examined immediately with an Olympus BX50F microscope (Olympus Europa, Hamburg, Germany). Quantitative data of vascular traits (vessel density per unit area and vessel lumen area per the entire growth ring) were determined with NIS‐Elements AR 3.0 image analysis software (Laboratory Imaging, Prague, Czech Republic) as described in Ďurkovič & Mišalová (). Mean theoretical relative conductivity (RC) was calculated according to Tyree & Zimmermann () as the fourth power of the equivalent circle diameter of the vessel lumen.…”
Section: Methodsmentioning
confidence: 99%